An experience of vocational guidance and counseling for youth employment program - Deza Villanueva, Sabina (2014)
Young people from marginalized social sectors today are undergoing a major crisis poverty fosters a situation of inequality among youth in their transit through the educational system, a split between young workers is generated and attend school less one hand , and students studying and have free time and access to material and symbolic goods and services , on the other. These processes of exclusion are no strangers to the future direction of the Young and the traffic school and levels of academic success or failure would condition the expectations and the development of a life plan . So we proceeded to evaluate a group of 90 young applicants to comprehensive scholarships ( made viable through an NGO funded by the International Cooperation) and identify those / as who are in top condition and support staff to receive during one year technical training, and at the conclusion of companies entering to work with previously established agreement. We believe that this proposal is for young men / women a viable option for your needs and expectations to face life and overcome adversity.